Systematic Review of Genetic Factors in the Etiology of Esophageal Squamous Cell Carcinoma in African Populations - Simba, Hannah; Kuivaniemi, Helena; Lutje, Vittoria; Tromp, Gerard; Sewram, Vikash (Frontiers in Genetics, 2019)
BACKGROUND: Esophageal squamous cell carcinoma (ESCC), one of the most aggressive cancers, is endemic in Sub-Saharan Africa, constituting a major health burden. It has the most divergence in cancer incidence globally, with high prevalence reported in East Asia, Southern Europe, and in East and Southern Africa. Its etiology is multifactorial, with lifestyle, environmental and genetic risk factors. Very little is known about the role of genetic factors in ESCC development and progression among African populations. The study aimed to systematically assess the evidence on genetic variants associated with ESCC in African populations. METHODS: We carried out a comprehensive search of all African published studies up to April 2019, using PubMed, Embase, Scopus and African Index Medicus databases. Quality assessment and data extraction were carried out by two investigators. The strength of the associations was measured by odds ratios and 95% confidence intervals. RESULTS: Twenty-three genetic studies on ESCC in African populations were included in the systematic review. They were carried out on Black and Admixed South African populations, as well as on Malawian, Sudanese and Kenyan populations. Most studies were candidate gene studies and included DNA sequence variants in 58 different genes. Only one study carried out whole exome sequencing of 59 ESCC patients. Sample sizes varied from 18 to 880 cases and 88 to 939 controls. Altogether over 100 variants in 37 genes were part of 17 case-control genetic association studies to identify susceptibility loci for ESCC. In these studies 25 variants in 20 genes were reported to have a statistically significant association. In addition, eight studies investigated changes in cancer tissues and identified somatic alterations in 17 genes and evidence of loss-off-heterozygosity, copy number variation and microsatellite instability. Two genes were assessed for both genetic association and somatic mutation. CONCLUSIONS: Comprehensive large-scale studies on the genetic basis of ESCC are still lacking in Africa. Sample sizes in existing studies are too small to draw definitive conclusions about ESCC etiology. Only a small number of African populations have been analysed, and replication and validation studies are missing. The genetic etiology of ESCC in Africa is, therefore, still poorly defined.